DNA-based Molecular Architecture with Spatially Localized Components - Muscat, Richard; Strauss, Karin; Ceze, Luis; Seelig, Georg (40th International Symposium on Computer Architecture, 2013)
Performing computation inside living cells offers life-changing applications, from improved medical diagnostics to better cancer therapy to intelligent drugs. Due to its bio-compatibility and ease of engineering, one promising approach for performing in-vivo computation is DNA strand displacement. This paper introduces computer architects to DNA strand displacement “circuits”, discusses associated architectural challenges, and proposes a new organization that provides practical composability. In particular, prior approaches rely mostly on stochastic interaction of freely diffusing components. This paper proposes practical spatial isolation of components, leading to more easily designed DNA-based circuits. DNA nanotechnology is currently at a turning point, with many proposed applications being realized. We believe that it is time for the computer architecture community to take notice and contribute.